BENTUK, FUNGSI DAN MOTIF PAKAIAN PENGANTIN TENUN INDRAGIRI DALAM UPACARA ADAT PERKAWINAN RENGAT PROPINSI RIAU - MASAYU UMI KALSUM, Dra. Zubaidah, M. Pd, Drs. Syafwandi, M.Sn (Serupa The Journal of Art Education, 2015)
Woven fabric Indragiri already existed since the time of the Malay kingdom Indragiri located in Riau mainland, with conventional motives and values shape the philosophy that has been inherent in people's lives Rengat. One of the functions of Indragiri woven fabric is used as a wedding dress in a traditional wedding ceremony Rengat. The existence of the wedding dress weaving looms Indragiri endangered and communities also lack an understanding of the function and meaning of wedding dress woven in a traditional wedding ceremony Indragiri Rengat.This study aimed to describe the form, function and motifs woven Indragiri wedding dress in traditional wedding ceremony Rengat .Methods that researchers use is through a qualitative approach. Subjects were informants who know about the object of research. Sources of data in the form of notes or recordings taken from informants interviewed, documentation and study of literature and photo footage from the wedding dress woven Indragiri in traditional wedding ceremony Rengat .The results showed that the basic motif of the wedding dress woven Indragiri generally sourced from flora and nature. There are eight motif name of the bride clothing Weaving Indragiri namely : pedada, tampuk manggis, pucuk rebung, tembangun, beawan, teluk berantai, betabo and tali air. Wedding dress woven motifs function Indragiri also visualize religious symbols and symbolic systems Malay indigenous life as portrayed in traditional wedding ceremony Rengat which includes evening events berinai, Berandam, Khatam Al - Quran, pick the groom, bridal march male and biting event .The conclusion of the research was the wedding dress woven motifs form Indragiri only resemble the flora and nature. Function woven motifs on wedding apparel, namely as a means of visualizing Indragiri religious symbols and symbolic systems Indragiri Malay customs